Comparative analysis of Polylactic Acid/Bamboo biocomposites manufactured by Additive Manufacturing and Compression Moulding Methods - D. Balaji; B. Arulmurugan; V. Bhuvaneswari; M. Sathishkumar (Journal of Materials Research and Technology)
Biodegradable composite material seeks enormous attention owing to its potential ability to replace synthetic materials and to be used in different applications. This article focuses on comparing properties of Polylactic acid (PLA)/bamboo biocomposites manufactured through compression moulding and Additive Manufacturing (AM) techniques. The weight fraction of bamboo fibers was taken as 20 % for both the manufacturing methods. The filament and the biocomposites were characterized by X-Ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR). The composites were tested for their mechanical properties such as Tensile strength, impact strength and hardness and tribological behaviour. Results revealed that the biocomposites specimen fabricated using compression moulding outperformed the AM specimen in terms of tensile strength by 30 % and hardness by 3.3 % but underperformed in terms of impact strength by 80 % and tribological behaviour by a significant margin. The biocomposites were applied to prepare door hinges using both the methods and the manufacturability of biocomposites were evaluated. The suitability of the manufacturing method to fabricate PLA/Bamboo biocomposites for structural application was evaluated comparatively.